Capital Expenditure : Role of Own-Source Revenue and Remaining Budget Surplus - Frisca Artha Ulina; Khairudin Khairudin; Riswan Riswan (International Journal of Economics, Business and Innovation Research, 2024)
This study was conducted with the intention of understanding the impact of local revenue and budget surpluses. The research was conducted in a number of districts and cities in Lampung Province. The research data was obtained from the website of the Directorate General of Fiscal Balance of Lampung Province in the form of budget realization reports during the 2018-2022 period, so the sampled data was 70. The data analysis method uses the SPSS test tool with the regression model. The results showed that Bandar Lampung had the highest PAD, and the lowest PAD was in West Pesisisr. The highest SiLPA was in South Lampung in 2019 and the lowest in 2021. Meanwhile, the highest capital expenditure is in Bandar Lampung, and the lowest in Metro. This study found that local revenue affects capital expenditure, while the remaining budget surplus has no effect on capital expenditure. The contribution of this research is that it is hoped that local governments will be able to maximize local revenue, which is used for the needs of the community, ensure that the budget issued is right on target, and carry out budget efficiency.